Teaching English For Quality Learning (Eurasian Journal of Learning and Academic Teaching, 2024)
Foreign language teaching, particularly English, holds significant importance worldwide, necessitating comprehensive attention to various aspects such as curriculum development, teacher education, instructional methodologies, and assessment practices. This article explores the multifaceted dimensions of language teaching, including syllabus design, teacher training, pedagogical approaches, and materials development. Insights from scholars like Nunan, White, Brown, Anthony, and others are synthesized to provide a nuanced understanding of language curriculum and instruction. Various language teaching methodologies, ranging from communicative to task-based approaches, are discussed alongside the challenges and considerations in their implementation. Furthermore, the article delves into the interplay between curriculum and materials development, highlighting the importance of adapting, adopting, or creating instructional materials to meet the diverse needs of language learners. By comprehensively addressing these aspects, language educators can navigate the complexities of teaching foreign languages effectively, contributing to enhanced language proficiency and educational outcomes.